Pengaruh Keandalan Pegawai Terhadap Penanganan Keluhan dan Implikasinya Pada Kualitas Pelayanan PLN Tebing Tinggi - Lubis, Syafridahani; Siahaan, Rumiris; Ketaren, Abednego (Economic Development Progress, 2022)
The background of this research is the results of observations regarding employee reliability, complaint handling and service quality at Tebing Tinggi City Branch PLN, such as the speed in responding to non-subsidized customer complaints. The aim of the study was to analyze the effect of employee reliability on complaint handling and its implications for service quality at PLN Branch, Tebing Tinggi City. This type of research is quantitative. The research population was non-subsidized PLN customers who had complaints at the Tebing Tinggi City Branch, namely 379 people. A sample of 80 people using the Slovin formula. The method uses accidental sampling. Data analysis using the SmartPLS program. The results of the study show that employee reliability directly influences complaint handling. Employee reliability influences service quality. Complaint Handling affects Service Quality Then indirectly complaint handling mediates the effect of employee reliability on service quality with p-values ​​of 0.000